STRENGTHENING READING COMPREHENSION AND INTEREST THROUGH SQ3R STRATEGY USING WHATSAPP DURING PANDEMIC - D. Abdul Kohar; Andang Saehu; Lidwina Sri Ardiasih (University of Kuningan, 2022)
The study employed the pre-test and post-test control group design focusing on strengthening reading comprehension and reading interest during the pandemic time using WhatsApp platform through survey, question, read, recite and review (SQ3R) strategy. The participants were the students of ninth graders of MTsN 6 Cianjur who were selected randomly to be the experimental and control classes. The instruments were the pre-post reading comprehension test and reading interest questionnaire especially on three dimensions; situational, individual and topic. The validity and reliability of both instruments were confirmed before applying them in the study. The analysis revealed that significant score (2 tailed) or (P) of post-reading comprehension test obtained by both experimental and control classes was 0%. Since it was less than 5%, the significant difference was confirmed, and the result quality of experimental class on reading comprehension was higher than control class. It decided that SQ3R strategy had strengthened reading comprehension skill. Moreover, all significant scores (2 tailed) or (P) of post-reading interest questionnaire on three dimensions obtained by both experimental and control classes were 0%. As they were less than 5%, the significant difference was confirmed, and the result quality of experimental class on reading interest was higher than control class. It exposed that SQ3R strategy had strengthened reading interest. Therefore, SQ3R strategy strengthened reading comprehension skill and reading interest using WhatsApp platform. Furthermore, SQ3R strategy was an alternative reading strategy in the pandemic time. However, the stakeholder should support it by providing free internet access and other requirements, and the study should be deepened by conducting other research especially qualitative study to enrich the scope of research. Keywords: SQ3R strategy; reading comprehension; reading interest; pandemic time; WhatsApp.